Development of the residual knowledge tests on the general course of physics for the students of the National Research University MPEI - Irina V. Mursenkova; Olga I. Lubenchenko; Konstantin M. Lapitsky (Вестник Московского Университета. Серия 20: Педагогическое образование)
Background. Teaching a general course of physics in a technical university is aimed at developing a holistic system of knowledge and skills in future engineers. Monitoring the quality of the educational process and checking the assimilation of physical knowledge in students are important components of the educational process. Distance testing as a part of distance education technologies has a significant potential for controlling knowledge in physics and mathematics disciplines, for improving acquired skills and abilities.